PERSEPSI MAHASISWA POLITEKNIK PERKAPALAN NEGERI SURABAYA MENGENAI PENGARUH KEIKUTSERTAAN ORGANISASI TERHADAP KEAKTIFAN PERKULIAHAN MAHASISWA - Alma Lia Hakim; Savina Dewi Firnanda; Gandes Rahma Firdausa; Denny Oktavina Radianto (KOLONI, 2023)
Organization is a form of implementing the role of students in the campus world, which is used as a means of self-development for students to improve reasoning and knowledge. Students who organize use various ways to overcome their problems, and are usually good at managing stress. But not all students can overcome the stress experienced while participating in organizations and lectures. Students who tend to experience stress are caused by several factors, namely conflict between roles which causes them to be unable to divide their time between lectures, assignments, and organizations that affect academic grades. The purpose of this research is to find out the perceptions of PPNS students regarding the influence of organizational participation on the lecturing activity of semester 4 PPNS students. The design of this research is a qualitative research using a questionnaire as research material. The sampling technique uses a non-probability sampling method with purposive sampling. From our research analysis, it was concluded that the majority of PPNS students joined the organization very well without disturbing their activeness in carrying out lectures on campus, and by participating in PPNS student organizations they had a positive impact in supporting life. However, the majority of PPNS students feel that they are behind in class due to organizational activities that finish at night after class, so students do not have time to study further material. Beside that, the majority of students feel sleep deprived, which is caused by many lecture assignments and organizational activities that finish late at night. Keywords: students, organizations, lecture activity, mental health, stress